2019
DOI: 10.1111/icad.12345
|View full text |Cite
|
Sign up to set email alerts
|

Mapping species distributions in 2 weeks using citizen science

Abstract: Ecological citizen science initiatives are growing in popularity with the increasing realisation of the potential for occurrence records to contribute information on biodiversity. Citizen science data are, however, justifiably criticised for misidentification, uneven sampling, incomplete detection or selective reporting. Here, we test the accuracy of citizen science data for UK social wasp (Vespinae) species’ distributions. We compared data collected over 2 weeks by members of the public setting out baited tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…A study demonstrated that within only two years of data gathering by citizen scientists, range size estimates (extend of occurrence and area of occupancy) were comparable to a long-term study [71]. However, during this study there might be a high prevalence of reports originated from human settlements resulting in an urban bias [4] as the present data set lacks occurrences in remote areas. Such uninhabited areas are often under-sampled in the frame of CSPs, which can lead to misinterpretation of the distribution data concerning population size, abundancy and habitat preferences [2].…”
Section: Potential Biases and Further Potential Of Cs Datamentioning
confidence: 46%
See 1 more Smart Citation
“…A study demonstrated that within only two years of data gathering by citizen scientists, range size estimates (extend of occurrence and area of occupancy) were comparable to a long-term study [71]. However, during this study there might be a high prevalence of reports originated from human settlements resulting in an urban bias [4] as the present data set lacks occurrences in remote areas. Such uninhabited areas are often under-sampled in the frame of CSPs, which can lead to misinterpretation of the distribution data concerning population size, abundancy and habitat preferences [2].…”
Section: Potential Biases and Further Potential Of Cs Datamentioning
confidence: 46%
“…Another point of criticism of CS programs that are focusing on species distribution data are spatial biases due to uneven sampling [99]. In contrast, recent projects show that CS programs are often less spatially biased than long-term studies or global platforms utilized mainly by experts [4,98]. Furthermore, it has been shown that CSP are fast and effective tools investigating distributional ranges of elusive species.…”
Section: Potential Biases and Further Potential Of Cs Datamentioning
confidence: 99%
“…Although the project was intended to understand wasp species distribution across the country, and to provide data to support conservation, the project was aggressively criticized for killing pollinators (Barkham, 2017). In fact, the project captured no queens, had a very limited by-catch and just 2 weeks of citizen engagement resulted in data comparable to four decades of expert sampling (Sumner, Bevan, Hart, & Isaac, 2019).…”
Section: Chang Ing At Titude S To Inverteb R Ate Smentioning
confidence: 99%
“…) or the “big wasp survey” to sample wasp populations across the United Kingdom (bigwaspsurvey.org, Sumner et al. ).…”
Section: Challenges and Outlookmentioning
confidence: 99%